Respostas
respondido por:
1
Resposta:
Explicação passo a passo:
(A + B) =
( 2 ) ( 1 ) ( 2 + 1) ( 3 )
I 6 I + I 6 I = I 6 + 6I = I 12 I
( 3 ) ( 2 ) ( 3 +2 ) ( 5 )
(A + B) - C =
( 3 ) ( 0 ) ( 3 - 0 ) ( 3 - 0 ) ( 3 )
I 12 I - I 4 I = I 12 - 4 I = I 12 - 4 I = I 8 I
( 5 ) ( - 2 ) ( 5 - (- 2)) ( 5 + 2 ) ( 7 ).
( 3 )
A + B - C = I 8 I
( 7 ).
mayconplay77432:
Amigo você pode resolver as outras questões que eu acabei de postar, por favor?
Perguntas similares
3 anos atrás
3 anos atrás
3 anos atrás
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás